Transporte de Nutrientes e sólidos suspensos na bacia do Rio Piancó Piranhas Açu - Ferreira, Paloma Mara de Lima; Sousa, Thâmara Martins Ismael de; Garrido, José Wagner Alves; Queiroz, Manoel Moises Ferreira de; Ismael, Luara Lourenço (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2013)